Trends in Internal Migration in Romania and Spain: How Different Are They? - Bunea, Daniela (Richtmann Publishing, 2012)
Internal migration is important from two perspectives: first, which are its motivations and, secondly, which are itsconsequences on regional economic growth. Theoretically, between internal migration and economic growth there is a bidirectionalrelationship. The purpose of this paper is to make a comparative study Romania-Spain in order to establish the main differencesbetween them and the reasons beyond differences. The choice for these two countries has its roots in the different timing of EUaccession and in their socio-economic heterogeneity. The research method is a quantitative comparative analysis using national andcounty/provincial data which takes account of inter and intra-regional streams, the evolution of migration (both absolute and relative), thepermanent or temporary existence of regional poles of attraction, the migration structure by sex and by age. Moreover, I will try toelucidate whether regional gaps in income and unemployment influence somewhat the decision to migrate using a dynamic econometricappraisal. The main results point out at a domination of intra-flows over inter-flows, an oscillatory evolution of migration, the existence ofreduced poles of attraction and a higher willingness of younger people to migrate in both Romania and Spain. Instead, the two countriesare different as regards the much higher propensity to migrate of Spanish residents. Also, women migrate more than men in Romaniawhile the contrary happens in Spain; also, the difference between sexes is greater in Romania. The System GMM estimations reveal thatin-migration rate exhibits state dependence and only GDP gaps motivate mobility in both countries.